Enhancing construction project management through cognitive science andnNeuroimaging: A comprehensive literature review - Kisi, Krishna; Sulbaran, Tulio (American Journal of STEM Education, 2025)
While substantial advances have been made in Cognitive Science and Neuroimaging, a notable gap remains in assessing cognitive status within the construction sector. This paper aims to demonstrate the considerable benefits of interdisciplinary approaches in enhancing project management effectiveness and outcomes by examining the complex interplay between cognitive processes, decision-making, and project management. ​Key findings indicate that cognitive status plays a critical role in the performance of construction workers, underscoring the necessity of prioritizing cognitive well-being in project strategies.​ Furthermore, the review highlights a deficiency in objective tools for evaluating cognitive status and proposes the adoption of neuroimaging technologies as a solution. By integrating neuroscientific insights with management practices, leaders can enhance training, team dynamics, and risk assessment, ultimately improving decision-making and productivity in construction project management.